PYRIDOXINE-INDUCED BLOOD INDICES OF WHITE RATS UNDER THE INFLUENCE OF IONIZING RADIATION - Костюк, С.С. (World of Medicine and Biology, 2014)
The article from the research proved that radiation negatively affects the blood leukogram of white rats. The use of exogenous pyridoxine reduces the negative effect of gamma radiation, which affects the content of individual forms of leukocytes and increases the number of formed elements and the concentration of hemoglobin.
Keywords: gamma-radiation rat erythrocytes; leukocytes; lymphocytes; neutrophils